Giant shape- and size-dependent compressive strength of molybdenum nano- and microparticles. (1st October 2020) - Sharma, A.; Kositski, R.; Kovalenko, O.; Mordehai, D.; Rabkin, E.
Abstract: The ability to process metallic samples at the sub-micrometer scale raised the strength limits of pure metals to the Giga Pascal (GPa) range. Here, we fabricated Mo nanoparticles with a giant compressive strength surpassing the previous strength records of metallic materials. Round and faceted particles were produced by manipulating the annealing atmosphere during two-stage solid-state dewetting of Mo thin films deposited on sapphire. The round particle underwent a huge elastic deformation before yielding abruptly. Using finite element analysis, we found that the resolved shear stress on a 112〈110〉 slip system beneath the punch reaches an enormous value of 20±1 GPa at yield, regardless of particle size. The faceted nanoparticles, contrarily, followed a "smaller is stronger" rule, with uniaxial compressive strength of up to 46 GPa for the smallest nanoparticles. Molecular dynamics simulations indicated that the size effect diminishes with increasing roundness of the particle edges. This work demonstrates how shape and size of particles can be manipulated to achieve giant strength. Graphical abstract: Image, graphical abstract